'UF-331' and 'UF-340' - Two University of Florida Dwarf Caladium Varieties for Containers and Landscapes - Zhanao Deng (EDIS)
ENH-1109, a 7-page illustrated fact sheet by Zhanao Deng, describes these two new lance-leafed caladium varieties with novel combinations of foliar characteristics — their origin, description, tuber production, container forcing and performance, landscape performance, recommendations and availability. Includes references. Published by the UF Department of Environmental Horticulture, January 2009.